The development of geometry concepts understanding based on NCTM reference in learning using discovery learning model - Suyitno, Hardi; Utami, Eka Nurul; Veronica, Rahayu Budhiati (Department of Mathematics, Universitas Negeri Semarang, 2019)
Mathematics Concepts Understanding is an important foundation for solving mathematical and everyday problems. In reality, students’ mathematics concepts understanding are not optimal. Learning based on NCTM standard is effective to help students in understanding mathematics material. Discovery Learning is suitable to be used to understand the development of students' conceptual understanding of geometry. The purpose of this study was to find out the development of geometry concepts understanding in Discovery Learning. The research was qualitative. The subjects of this study were 6 students. The 2 subjects were selected for each upper, middle and lower class based on the results of the initial test of understanding geometric concepts in one of the seventh grade in a junior high school in Rembang which had previously been ranked.The results showed that (1) both U-12 and U-17 subjects were able to fulfill all indicators of understanding geometry concepts 1 to 7 very well, (2) the two middle-class research subjects were U-19 subjects and U-24 have been able to fulfill all indicators of understanding geometric concepts well, (3) the two lower class research subjects namely U-30 and U-10 were finally able to fulfill all indicators of understanding geometric concepts from 1 to indicator 7 even though they were not good and rather slow compared to the upper and lower groups. They still experienced some difficulties, especially in the indicators of understanding the 4th, 5th and 7th concepts.